2005
DOI: 10.1111/j.1559-1816.2005.tb02207.x
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Surgery: A Common and Accepted Form of Self-Improvement?1

Abstract: The pursuit of beauty through alteration of physical appearance is a growing trend. Rates of cosmetic surgery have soared, suggesting that surgery is a common, acceptable solution to the desire for self-improvement. Despite indications that surgeries are increasing in frequency, there have been few empirical investigations about popular attitudes toward cosmetic surgery. In the present study, 302 female undergraduate students were surveyed. Approximately 3% of the sample had undergone cosmetic surgery themselv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
3
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 23 publications
10
119
3
9
Order By: Relevance
“…The rapid growth in cosmetic surgical procedures seems to reflect the public's blooming acceptance of cosmetic surgery as a mode of self-improvement (Delinsky, 2005). Given the multifarious potential costs associated with elective cosmetic surgery procedures, it is very important that researchers gain a more comprehensive understanding of the motives that underlie these decisions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid growth in cosmetic surgical procedures seems to reflect the public's blooming acceptance of cosmetic surgery as a mode of self-improvement (Delinsky, 2005). Given the multifarious potential costs associated with elective cosmetic surgery procedures, it is very important that researchers gain a more comprehensive understanding of the motives that underlie these decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to attractive others can affect our mate-preferences and interests (Kenrick, Neuberg, Zierk, & Krones, 1994) as well as our own body satisfaction (Hawkins, Richards, Granley, & Stein, 2004). Moreover, media exposure has been found to influence attitudes and intentions surrounding cosmetic surgery (Delinsky, 2005;Henderson-King & Brooks, 2009). It is interesting that our mediation model applied to men for both attitudes toward cosmetic surgery and willingness to spend on cosmetic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um componente importante do autoconceito é a imagem, a percepção e a avaliação do próprio corpo, em termos de elementos como o tamanho e a capacidade de atração (Fisher, 1986). Delinsky (2005) argumentou que quanto maior é a importância da aparência para a autoestima das mulheres, maior é a aprovação delas em relação à cirurgia estética. Segundo o autor, foi constatado também que quanto maior é a autoestima da mulher, maior é a sua aprovação para com a cirurgia estética.…”
Section: Autoestima E Autoavaliação Do Corpounclassified
“…It is known that acceptance of plastic surgery is positively correlated to exposure to me dia messages 5 and exposure to individuals, particularly those to whom the individual is close, who have previously undergone this type of surgery 6 . Sarwer et al 7 identified a po sitive association between acceptance of cosmetic plastic surgery in line with exposure to and influence by the media regarding attitudes toward plastic surgery.…”
Section: Introductionmentioning
confidence: 99%